Impact of In Ovo Adenosine Triphosphate (ATP) Injection on Digestive and Antibody-Related Organ Development and Health in Post-Hatch Sentul Chickens - Yudiputra , Muhammad Ilham; Ulfah, Maria; Krisnan, Rantan (Faculty of Animal Science, Universitas Brawijaya, 2025)
The Sentul chicken is a native Indonesian breed known for its good genetic potential as a broiler chickens but often has suboptimal growth and feed efficiency. In Ovo feeding (IOF), the administration of nutrients directly into the egg during incubation offers an alternative strategy to enhance embryonic development. This study aimed to evaluated the effects of ATP injection via IOF on the development of digestive and immune organs, as well as the health status of post hatching Sentul chickens. A commercial ATP mixture containing ATP, vitamin B12, Mg-aspartate, K-aspartate, and sodium selenite was injected into 200 eggs on day 18 of incubation. Observations included those of digestive organs (duodenum, jejunum, ileum, cecum, and proventriculus), animal-related organs (bursa of the fundus and spleen), and blood profiles (erythrocytes, leukocytes, and leukocyte differentiation). The results revealed that ATP injection significantly improved (P<0.05) the jejunum weight and the lengths of the jejunum, cecum, and proventriculus. Early post hatching erythrocyte and leukocyte counts also increased significantly, whereas leukocyte differentiation revealed increased immune activity through changes in heterophil, lymphocyte, monocyte, and H/L ratios. These findings indicate that IOF with ATP supports organ development and strengthens immunity and health, suggesting a promising approach to improve the quality of day-old chicks and productivity in local poultry farming.